Biomass (Ash Free Dry Mass/AFDM) of Periphyton in the Ceramic Substrate in the Salo River, Salo District, Kampar Regency, Riau Province - Febyando, Radieka; Simarmata, Asmika H.; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Periphyton is a sessile microscopic organisms that attach on certain substrate. A research aims to understand the biomass of periphyton in the SaloRiver based on its Ash Free Dry Mass (AFDM) in ceramic substrate, a study has been carried out in July-August 2015. There were 3 stations, namely Station 1 (in the upstream), Station 2 (in the midlle part of the stream) and Station 3 (in the downstream) for placing the ceramic substrate and for taking the water samples. Samplings were conducted 4 times, once/week. The periphyton samples were scrapped from the surface of ceramic substrate (10 cm x 3 cm). The number of ceramic sampled in each station were 10, 7 and 5 pieces in Station 1, Station 2 and Station 3 respectively. Results shown that periphyton biomass in the Salo River in general was around 0.449–2.834 mg/cm2. The periphyton biomass in the ceramic substrate placed in the Station 1, Station 2 and Station 3 was significantly different, there were 0.449 mg/cm2, 1.442 mg/cm2, and 2.834 mg/cm2 respectively. In general, the periphyton biomass in the downstream was higher than those of the other areas, indicated that the productivity in the downstream was the highest.Keywords: Salo River, Periphyton, Ceramic Substrate, Biomass (AFDM)